Effectiveness of language training and non-invasive brain stimulation on oral and written naming performance in Primary Progressive Aphasia: A meta-analysis and systematic review. (January 2020) - Cotelli, Maria; Manenti, Rosa; Ferrari, Clarissa; Gobbi, Elena; Macis, Ambra; Cappa, Stefano F.
Highlights: Language training in patients with PPA. Long-lasting effects of language training. Effects of language training combined with tDCS. Abstract: The aim of this systematic review and meta-analysis is to examine the efficacy of language training, alone or in combination with non-invasive brain stimulation techniques, designed to improve oral and written naming abilities in Primary Progressive Aphasia (PPA), and to investigate whether gains can be maintained over time and generalize to untrained items. An electronic database search was conducted up to 31 st of May 2019. Forty-three articles on language training alone and seven articles on the combined treatment fitted the inclusion criteria for the systematic review. Results indicated that language training, alone or in combination with transcranial direct current stimulation (tDCS), improves oral naming accuracy for trained items in patients with PPA, with a long-term maintenance of the gain over time. Only language training combined with tDCS improves oral naming accuracy for untrained items. Considering written naming abilities, language training combined with tDCS improves performance for both trained and untrained items, immediately after training and at follow-up.